A Generalised Statistical Convergence: Gokulananda Das, B. K. Ray, Sakambari Mishra - Team, Support (Thai Journal of Mathematics, 2014)
The object of this present paper is to dene and study generalised statistical convergence for the sequences in any locally convex Hausdorff space X whose topology is determined by a set Q of continuous seminorms q and their relation with the nearly convergent sequence space using a bounded modulus function along with regular and almost positive method.